2011
DOI: 10.1007/s12011-011-9259-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wastewater Irrigation on Chemical and Physical Properties of Petroselinum crispum

Abstract: The present study was carried out to assess the impact of wastewater on parsley (Petroselinum crispum). The parameters determined for soil were pH, electrical conductivity (EC), soil organic matter (SOM), nutrient elements (Ca, Mg, Na, K, Mn, Cu, Zn, and Fe), and heavy metals (Cd, Cr, Ni, and Pb), while the parameters determined for the plant included pigment content, dry matter, nutrient element, and heavy metals. SOM, EC, and clay contents were higher, and pH was slightly acidic in soil treated with wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…was measured in June than in October. The observations presented in this study are also consistent with the findings of Fargašova 49 who examined the aboveground parts of Sinapis alba L. seedlings, however, our results are not in agreement with the findings of Keser et al 54 in Lepidium sativum L. Different effects of pollution on Chl b in relation to Chl a have been reported in many studies. 52,54 However, the different responses of Chl a and Chl b are not unexpected, since different types of pollution exert different effects on the pigment content, hence the response of a plant can be attributed to the interaction between various types of pollutants as well as abiotic factors (high temperature, drought, intense insolation, etc.…”
Section: Photosynthetic Pigmentssupporting
confidence: 77%
See 1 more Smart Citation
“…was measured in June than in October. The observations presented in this study are also consistent with the findings of Fargašova 49 who examined the aboveground parts of Sinapis alba L. seedlings, however, our results are not in agreement with the findings of Keser et al 54 in Lepidium sativum L. Different effects of pollution on Chl b in relation to Chl a have been reported in many studies. 52,54 However, the different responses of Chl a and Chl b are not unexpected, since different types of pollution exert different effects on the pigment content, hence the response of a plant can be attributed to the interaction between various types of pollutants as well as abiotic factors (high temperature, drought, intense insolation, etc.…”
Section: Photosynthetic Pigmentssupporting
confidence: 77%
“…Although, many authors have shown that an increased content in polluting agent leads to chlorophyll inhibition 11,49-51 either through direct inhibition of several enzymatic steps or as a result of substitution of the central Mg ion, 52 several studies have shown that the exposure to heavy metals induces oxidative stress which is accompanied by an increase in the chlorophyll content. [52][53][54] For example, Kalaikandhan et al 55 examined the effects of different Zn concentrations on the photosynthetic pigment content in Sesuvium portulacastrum leaves during 120 days and established that an increase in Chl a accompanied the increase in the concentration of Zn in the substrate from 100 to 300 mg kg -1 , with which our results are in good agreement. Likewise, Petrova 56 tested the pigment response to urban air pollution in birch leaves and found that the highest concentrations of chlorophyll were present in plants growing in environments with a medium level of urbanization and moderate exposure to road traffic pressure.…”
Section: Photosynthetic Pigmentssupporting
confidence: 70%
“…Furthermore, ingestion of parsley should be discouraged in pregnancy, lactating mothers and in individuals on opiods, lithium salts, diuretics and warfarin therapy due to potential drug-herb interaction [4,9,34]. Because Parsley bio-accumulate toxic heavy metals [12], it’s cultivation should not be done on soil irrigated with untreated waste water.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration should also be giving to sources of plant cultivation due to the fact that resorption of heavy metals by the plants has been observed in soil irrigated with untreated waste water making the plant a potential source of heavy metal toxicity [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The highest water use effi ciency for wheat, obtained in the 75 % wastewater containing irrigation treatment under the fertilised condition and the raw wastewater-irrigated treatment under the non-fertilised condition in Bangladesh, demonstrated the most effective use of water in these treatments (Mojid et al 2012 ). Keser and Buyuk ( 2012 ) indicated wastewater in Turkey was not suitable for irrigation of parsley, because it had negative effects on plant and caused heavy metal accumulation. Herbaceous crops irrigated with wastewater can produce appreciable biomass and energy yields.…”
Section: Cropsmentioning
confidence: 99%